The macroeconomics of "financialisation" and the deeper origins of the world economic crisis - Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
In recent years, the interdisciplinary literature on financialisation has become one of the most quickly developing areas in the social sciences, including (Post Keynesian) macroeconomics. We discuss the relevance of the financialisation hypothesis in a non-technical manner from a macroeconomic perspective. Our interpretation of financialisation allows one to analyse the fundamental changes that the US and other economies have undergone over the past three decades or so. In particular, it helps to understand how the US economy has turned from a "debt-led" system, combining relatively weak physical investment activity, strong consumer spending, high income inequality and increasing indebtedness of firms and private households, to a "debt-burdened" system. In light of the current world economic crisis, the Keynesian financialisation hypothesis now seems to be increasingly shared among policy makers and economists.
urn:nbn:de:101:1-201101312735
Keywords: 330